(untitled) (Journal of Bangladesh Academy of Sciences, 2025)
In the current study, ten F1 hybrids and their five parents were evaluated for agronomic, post-harvest, and nutritional traits. Significant genetic variation was observed among the traits, which grouped the planting materials into four phylogenetic clades. High heritability, coupled with high genetic advance was recorded for fruits per plant (99.61% and 170.55%), single fruit weight (99.06% and 102.09%), and vitamin C content (99.98% and 177.53%), suggesting that these traits are governed predominantly by additive gene action. Pearson’s correlation and path coefficient analyses identified fruit diameter, number of secondary branches, single-fruit weight, and skin thickness as key traits positively associated with fruit yield, while increased skin thickness also contributed to enhanced shelf-life. Based on mean performance, the hybrids BT-15 × BT-3, BT-8 × BT-15, and BT-8 × BT-14 emerged as promising candidates for high yield. In addition, BT-8 × BT-11 and BT-8 × BT-15 exhibited superior shelf life and nutritional quality. Overall, the findings highlight the potential of integrating yield, post-harvest, and nutritional traits into selection indices for the development of superior tomato hybrids. J. Bangladesh Acad. Sci. 49(2); 255-269: December 2025